Comparative analysis of waste tire pyrolysis oil and gasoline as low reactivity fuel in RCCI engine - Firat, Mujdat; Okcu, Mutlu; Celik, Okan; Altun, Sehmus; Varol, Yasin (Taylor & Francis Inc, 2023)
The utilization of alternative fuels in internal combustion engines has gained significant attention due to concerns about energy security and environmental sustainability. Waste tire pyrolysis oil (WTPO) is a potential alternative fuel that can be produced from waste vehicle tires through a pyrolysis process. In this study, the possible use of WTPO in a diesel engine operating under Reactivity Controlled Compression Ignition (RCCI) mode was investigated. In the study, the use of WTPO as a low-reactivity fuel in RCCI engines is examined, highlighting the importance of innovative approaches to alternative fuels with varying reactivity levels for effective combustion control and emission reduction. In the experimental work, WTPO was tested at different energy rates of 15%, 30%, and 45% into the intake port using the PFI system, while conventional diesel fuel was injected directly into the cylinder by the CRDI system. The tests were carried out under different engine load conditions while maintaining a constant engine speed of 2400 rpm. The performance, combustion, and emission characteristics of the engine were analyzed and compared between WTPO and conventional gasoline fuel as LRF. The study results show that using WTPO in RCCI operation with sustainable ringing intensity leads to significant increases in Brake Thermal Efficiency (BTE) compared to gasoline usage, with BTE increments of up to 5%, 3.3%, and 6.3% observed with increasing engine load. Furthermore, WTPO usage in RCCI engines effectively reduced hydrocarbon (HC) emissions, addressing a significant issue, and maintaining the known benefits of reactivity-controlled combustion. These findings suggest that WTPO can be utilized as a viable low-reactivity fuel in RCCI engines with acceptable performance, combustion, and emission characteristics.
Keywords: RCCI; diesel engine; Waste Tire Pyrolysis Oil (WTPO); emissions; combustion